2019
DOI: 10.1073/pnas.1816685116
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural verticilide enantiomer inhibits type 2 ryanodine receptor-mediated calcium leak and is antiarrhythmic

Abstract: Ca2+ leak via ryanodine receptor type 2 (RyR2) can cause potentially fatal arrhythmias in a variety of heart diseases and has also been implicated in neurodegenerative and seizure disorders, making RyR2 an attractive therapeutic target for drug development. Here we synthesized and investigated the fungal natural product and known insect RyR antagonist (−)-verticilide and several congeners to determine their activity against mammalian RyR2. Although the cyclooligomeric depsipeptide natural product (−)-verticili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 64 publications
6
69
0
Order By: Relevance
“…For example, human cardiomyocyte models of CPVT generated from patient-specific induced pluripotent stem cells (iPSCs) also exhibit DADs and action potentials triggered by spontaneous calcium release (Novak et al 2012(Novak et al , 2015. Drug efficacy in isolated ventricular cardiomyocytes can predict anti-arrhythmic efficacy in mouse models and in humans with CPVT (Knollmann, 2011;Batiste et al 2019). Furthermore, CPVT patients frequently present with atrial tachycardia or atrial fibrillation that can occur prior to or during their ventricular tachycardia (Leenhardt et al 1995).…”
Section: Ventricular Cardiomyocytes As the Cellular Source Of Cpvtmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, human cardiomyocyte models of CPVT generated from patient-specific induced pluripotent stem cells (iPSCs) also exhibit DADs and action potentials triggered by spontaneous calcium release (Novak et al 2012(Novak et al , 2015. Drug efficacy in isolated ventricular cardiomyocytes can predict anti-arrhythmic efficacy in mouse models and in humans with CPVT (Knollmann, 2011;Batiste et al 2019). Furthermore, CPVT patients frequently present with atrial tachycardia or atrial fibrillation that can occur prior to or during their ventricular tachycardia (Leenhardt et al 1995).…”
Section: Ventricular Cardiomyocytes As the Cellular Source Of Cpvtmentioning
confidence: 99%
“…Dantrolene, a drug used clinically to treat hyperactive skeletal muscle calcium release, decreased exercise-induced ventricular ectopy in some but not all CPVT patients (Penttinen et al 2015). Our group recently reported J Physiol 598.14 the discovery of ent-verticilide, a cyclic depsipeptide that has nanomolar potency, is selective for RyR2 over RyR1, and exhibits anti-arrhythmic efficacy in vivo (Batiste et al 2019). Another promising drug target is the calmodulin-dependent serine-threonine protein kinase II (CaMKII) (Fig.…”
Section: Possible Future Cpvt Therapiesmentioning
confidence: 99%
“…Genetic analyses and findings led to the conclusion that chromosomal area of 1q42-q43 genes is probably closely connected to the function of ryanodine receptor (RyR)-calcium-release channels in cardiac tissues (Priori et al, 2001;Marks et al, 2002). Based on these aforementioned publications, it was suggested that potential inhibitors of RyR, especially RyR2, could be an important antiarrhythmic target for the development of new therapeutic agents (Bongianino et al, 2017;Batiste et al, 2019).…”
Section: The Ecg and Inherited Syndromesmentioning
confidence: 99%
“…However, other antiarrhythmic agents initially classified by Vaughan Williams (1975), which are used in clinical therapy against hypoxia-or ischemia-induced arrhythmias e.g., beta adrenergic receptor blockers and calcium channel antagonists, should be avoided for the therapeutic management of arrhythmias with prolonged QT interval. A promising future approach, under experimental conditions to manage the CPVTinitiated QT prolongation, was published by Batiste et al (2019) showing that an unnatural verticilide enantiomer inhibits the function of RyR2-mediated calcium leak, which inhibits QT prolongation, and prevents life threatening arrhythmias.…”
Section: Clinical Management Of Prolonged Qt Intervalmentioning
confidence: 99%
“…Although disputed by Bannister et al (2015) the most plausible explanation is that flecainide acts directly on RyR2 by blocking its open state, and thereby reduces the amount of Ca 2+ released during spontaneous openings of RyR2 channel clusters measured as Ca 2+ sparks (Hilliard et al, 2010). The hypothesis that flecainide inhibits RyR2 channels is supported by work indicating that flecainide suppresses RyR2-mediated SR Ca 2+ efflux (e.g., Ca 2+ spark mass) in permeabilized cardiomyocytes under experimental conditions that render Na + channels inactivated (Hilliard et al, 2010; Savio-Galimberti and Knollmann, 2015; Batiste et al, 2019). In contrast, Sikkel et al (2013) proposed that Na + channel block alone is responsible for Flecainide’s efficacy in CPVT.…”
Section: Discussionmentioning
confidence: 98%